Bacterial Content in Gut For Different Species of Fish Collecting From Tigris River in Baghdad City, Iraq - Nada W. Hammood; Israa AJ. Ibrahim (Tikrit Journal of Pure Science)
A bacteriological study was conducted on fish from May to October 2015. The total of  50 fishes were collected from Tigris River passing through Kurayat, Shawakah and  Utaifiah  at Baghdad City. There are seven species of fish  recorded were: Acanthobrama marmid, Alburnus mossulensis, Carasobarbus luteus, Cyprinus carpio, Garra elegans, Garra rufa and Planiliza abu. Selective media were used to identify the bacteria such as: CHROMagarTM Orientation (for Enterobacteriaceae and non- Enterobacteriaceae group), CHROMagarTM Vibrio and TCBS media (for Vibrio group), CHROMagarTM ESBL medium (forβ- lactamase production), and Xylose lysine deoxycholate agar (XLD) (for Salmonella spp.   In current study, the bacterial total count in the gut  of examined fishes ranging from 31 to 456 ×103 cell/ml. The  isolated bacteria belonged to Enterobacteriaceae are  Citrobacter amalonobicas, C. diversus, C. frundii, Edwardsiella tarda, Enterobacter agglomerans, E.cloacae, E.gergoviae, E.sakazaki, Escherichia coli, Klebsiella oxytoca, K. pneumoniae,  Proteus mirabilis, P. vulgaris, Providencia vettigen, Serratia marcesens and S.  rubidaea, while for Non- Enterobacteriaceae are Acinetobacter spp., Pseudomonas spp., Vibrio alginolyticus, V. cholera, V. parahaemolyticus and V. vulinficus. This study provides an overview of the bacterial gut contents of economic and non-economic fish.